Anion/Cation Co-(de)Intercalation in Ti3C2Tx Modified with Cobalt Phthalocyanine for Lithium-Ion Batteries - Duan Yuchen; Qin Jinwen; Cao Minhua (E3S Web of Conferences)
Due to the shortage of lithium resources and the requirement for high-energy density in lithium- ion batteries (LIBs), anion/cation co-(de)intercalation based on the incorporation of both anions and cations from the electrolyte is expected to be a viable solution. In this work, through cobalt phthalocyanine (CoPc) modification, Ti3C2Tx MXene utilizes cationic/anionic carriers for charge storage. Specifically, during the charging process, a reversible intercalation of PF6- anions occurs subsequent to the removal of Li ions. By unlocking the capability of anion/cation co-(de)intercalation, the as-designed Ti3C2Tx-CoPc anode exhibits significant merits in terms of storage capacity (achieving up to nearly 3-fold improvement over the Ti3C2Tx) and excellent rate performance. Our findings highlight new anion/cation co-(de)intercalation chemistry for MXenes.